Social factors associated with medication noncompliance in schizophrenic patients who attending psychiatric teaching hospitals - Ashoor, Fatin Ghani; Mohammed, SajaHashim (International Journal of Psychosocial Rehabilitation, 2020)
A descriptive cross-sectional study that was carried out during the period of March 20, 2019 to September 10, 2019. The study aim was to assess the level of medication non- compliance and the social factors associated with medication non- compliance among schizophrenic patients. A purposive (Non-Probability) sample of 150 schizophrenic outpatients was selected. Data were collected through the use of the constructed questionnaire and the process of the structured interview and administrative questionnaire The questionnaire was constructed as a main instrument, which consisted of three parts; the first part includes two sections which are the covering letter to obtain the agreement of patients to participate in the present study and the socio- demographic and clinical characteristics of the patients; the second part is the questionnaire with 20 items measure the social factors associated with medication non- compliance in schizophrenic patients; the third part of Questionnaire is concerned with medication non- compliance level in patients with schizophrenia. The study result found that social factors were moderately associated with non-compliance to medication among patients (75.3%). The findings also shows that high level of non-compliant to medication (60.7%). The study recommended strengthen psychiatric social work departments through adequate training and laying down infrastructure to ensure that the patients social assets are holistically assessed and utilized appropriately to enhance medication compliance and thus improve quality of life.